The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1966
DOI: 10.1128/jb.91.1.436-441.1966
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Serially Propagated Monkey Kidney Cell Cultures with Persistent Rubella Infection

Abstract: MAASSAB, H. F. (University of Michigan, Ann Arbor), AND J. A. VERONELLI. Characteristics of serially propagated monkey kidney cell cultures with persistent rubella infection. J. Bacteriol. 91:436-441. 1966.-A persistent infection of LLC-MK2 cells with rubella virus has been established and maintained for over 3 years. This "carrier culture," designated as LLC-MK2-RAL, possesses distinct morphological and biological characteristics when compared with the original uninfected LLC-MK2 line. The mechanism of viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1966
1966
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…Although it has been suggested that interferon may play a role in maintaining the persistent infection of cells by rubella virus in vitro (6,12,29), there are several reports of rubella viral persistence in the absence of detectable interferon (8,14,19,20). Our data indicated that neither the initiation nor maintenance of rubella viral persistence was due to the presence of interferon.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Although it has been suggested that interferon may play a role in maintaining the persistent infection of cells by rubella virus in vitro (6,12,29), there are several reports of rubella viral persistence in the absence of detectable interferon (8,14,19,20). Our data indicated that neither the initiation nor maintenance of rubella viral persistence was due to the presence of interferon.…”
Section: Resultscontrasting
confidence: 69%
“…Persistent infections with rubella virus have been reported previously for several cell lines (11,12,14,23,24,29). Because of experimental variations among laboratories, many of the data are either inconclusive or contradictory regarding the function of interferon in rubella viral persistence and interference against superinfection with heterologous viruses.…”
mentioning
confidence: 73%
“…Even the impairment induced by live virus could be prevented if the virus and its neutralizing antibody were added simultaneously to the lymphocytes (13). However, lymphocytes have been shown to allow replication of virus within the cell and to transmit the virus to daughter cells during cell division without the virus going through a surface transmission (6,53). Such daughter cells also appeared unresponsive to PHA stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Rubella virus carrier cultures have been induced in stable cell lines (37)(38)(39). Cell strains derived from certain tissues (skin and pharyngeal mucosa) of human embryos were also found to survive in a carrier state when experimentally infected with rubella virus (40).…”
Section: Discussionmentioning
confidence: 99%